Traditionalism and reformism polemic in Malay-Muslim religious literature - Rahimin Affandi Abdul Rahim (Islam and Christian-Muslim relations, 2006)
At the end of the twentieth century, the Muslim academic world has been faced with a polemic between traditionalism and reformism, to the extent that it has come to preoccupy most present-day scholars. Most modern studies on contemporary Islamic law have mainly concentrated on Muslim countries in the Middle East and the Indian sub-continent, but this study will look at Malaysia, which is a relatively new field of Islamic legal inquiry. The article will concentrate on historical events in Malaysia from 1900 until the 1940s and, on the basis of what these events revealed, will highlight the legal polemic initiated by Malayan Islamic reformism and traditionalism. The discussion will focus on three issues: first, the capacity of human reason to understanding Islamic teaching; second, the concepts of ijtihād and taqlīd; and third, attitudes towards classical Muslim fiqh.